Increasing situational awareness through nowcasting of the reproduction number - Andrea Bizzotto; Andrea Bizzotto; Giorgio Guzzetta; Valentina Marziano; Martina Del Manso; Alberto Mateo Urdiales; Daniele Petrone; Andrea Cannone; Chiara Sacco; Piero Poletti; Mattia Manica; Agnese Zardini; et al. (Frontiers Media S.A., 2024)
BackgroundThe time-varying reproduction number R is a critical variable for situational awareness during infectious disease outbreaks; however, delays between infection and reporting of cases hinder its accurate estimation in real-time. A number of nowcasting methods, leveraging available information on data consolidation delays, have been proposed to mitigate this problem.MethodsIn this work, we retrospectively validate the use of a nowcasting algorithm during 18 months of the COVID-19 pandemic in Italy by quantitatively assessing its performance against standard methods for the estimation of R.ResultsNowcasting significantly reduced the median lag in the estimation of R from 13 to 8 days, while concurrently enhancing accuracy. Furthermore, it allowed the detection of periods of epidemic growth with a lead of between 6 and 23 days.ConclusionsNowcasting augments epidemic awareness, empowering better informed public health responses.